Zero-Rating and Network Effects - Steffen Hoernig; Francisco Monteiro (International Telecommunications Society (ITS), 2019)
We consider internet service providers' incentives to zero-rate, i.e. do not count towards data allowances, the consumption of certain services, in the absence of payments from content providers. In a general model with various types of network effects, service substitutes or complements, monopoly and duopoly, we show that ISPs adopt zero-rating and that it increases consumer surplus and total welfare if network effects are strong enough. Capacity investment increases (decreases) with network effects if services are complements (substitutes). Under competition, the decision to zero-rate depends the residual network effect, which includes the impacts of spillovers and brand differentiation.
Keywords: D21; L51; L96; 330; Zero-rating; Network effects; Net neutrality; Capacity Investment